Fronteira e mobilidade: A Amazônia e suas pluralidades - Juliana Mota de Siqueira (2013)
The international Brazilian frontier area, including a total of 588 municipalities over 150 km long, has several peculiarities in relation to other regions of the country. For this reason, studies on the conformation socio-demographic, geopolitical, environmental, cultural and economic, are challenges that are intensified by national and transnational dimensions involved. These special conditions influence directly the conformation of the mobility of the population in the frontier areas of Brazil, other than traditional international migration with change of residence involving temporary dislocations with different regularities. A special case, which caught our attention for its population dynamics is the international border in the Brazilian Amazon, composed by 126 municipalities, inserted into a quite unique reality and still poorly studied. In this context, this paper aims to investigate the central phenomenon of recent demographic and social mobility in the area of international frontier in the Brazilian Amazon. It covers: i) a theoretical discussion of the concept of "frontier" and some of its forms measured in the Amazon Frontier Zone, ii) a general description of the geographic profile, demographic and economic development of the Amazon Frontier Area, compared with the rest of the Frontier Areas in Brazil, to demonstrate the heterogeneous nature of the region, iii) the theoretical and methodological discussion of the concept of mobility and one of its most used, that being migration; iv ) a brief historical overview about the occupation of the Amazon frontier and its connection with the ways that the spatial mobility of its population has happened contemporaneously in the region v) the mapping and characterization of internal and international mobility in the Area of the Amazon Frontier. All these points were developed from data provided by the Brazilian Demographic Censuses from 2000 and 2010.